Blood Leukocytes in Young and Aged Rats After Whole Body Cryostimulation (–120°C) - Lomako, Victoria; Pirozhenko, Liudmyla (Problems of Cryobiology and Cryomedicine, 2021)
The whole body cryostimulation (WBC) (–120°C) induces significant changes in blood leukocyte parameters in young and aged rats (total leukocyte number (leukocytosis or leukopenia); quantitative and qualitative correlation of their types, and shift direction in leukocyte formula); appearance of immature, plasm and polychromatophilic cells, cytoplasm plasmatization in some leukocytes, and changes in the integral leukocyte indices. The direction and severity of these changes depend on animals age (6–7 or 18–20 months old), number of the WBC sessions (1, 2 or 3), terms of observation (day and week) and mainly indicates physiological alterations in a body, that may be associated with the strain of involved functional systems and stress. In aged rats only, 24 hrs after the 2nd WBC session the lymphocyte percentage corresponded to a lower control value, thus indicating the training response formation at this stage. The integral leukocyte indices of aged rats underwent considerably smaller changes if compared with the young ones, especially in 24 hrs and a week after the WBC; the Garkavi adaptation index increased only in aged rats and just 24 hrs after the 3rd WBC session. Probl Cryobiol Cryomed 2021; 31(1): 023–037